2015
DOI: 10.1186/s12862-015-0424-z
|View full text |Cite
|
Sign up to set email alerts
|

Repeated evolution and the impact of evolutionary history on adaptation

Abstract: BackgroundWhether natural selection can erase the imprint of past evolutionary history from phenotypes has been a topic of much debate. A key source of evidence that present-day selection can override historically contingent effects comes from the repeated evolution of similar adaptations in different taxa. Yet classic examples of repeated evolution are often among closely related taxa, suggesting the likelihood that similar adaptations evolve is contingent on the length of time separating taxa. To resolve thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 44 publications
9
76
0
Order By: Relevance
“…Furthermore, more than 80% (40/49) of cases occur at sub-family taxonomic units (species/genus/subfamily/family). Previous observations of repeated evolutionary events across other traits including morphology, physiology, and life history shows a similar trend, indicating that behaviors are not subject to evolutionary processes distinct from these other phenotypes (Vermeij, 2006;Ord and Summers, 2015). In addition we find a significant positive correlation between clade size and conversion number (r 2 = 0.46; p = 0.001) but not between evolutionary divergence time and conversion (r 2 = 0.11; p = 0.46).…”
Section: Key Concept 3 | Phenotypic Transitionssupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, more than 80% (40/49) of cases occur at sub-family taxonomic units (species/genus/subfamily/family). Previous observations of repeated evolutionary events across other traits including morphology, physiology, and life history shows a similar trend, indicating that behaviors are not subject to evolutionary processes distinct from these other phenotypes (Vermeij, 2006;Ord and Summers, 2015). In addition we find a significant positive correlation between clade size and conversion number (r 2 = 0.46; p = 0.001) but not between evolutionary divergence time and conversion (r 2 = 0.11; p = 0.46).…”
Section: Key Concept 3 | Phenotypic Transitionssupporting
confidence: 78%
“…This owes largely to the fact that the original definitions predated the advent of modern molecular methods (Losos, 2011;summarized in Table 1). Recently authors have suggested replacing the terms with others, including repeated evolution (Gompel and Prud'homme, 2009;Ord and Summers, 2015), homoplasy (Wake et al, 2011), and phylogenetic replication (Kopp, 2009). Arendt and Reznick (2008), on the other hand, collapse the distinctions altogether under one banner-convergent evolution-arguing that the convergent vs. parallel split represents a false dichotomy.…”
Section: Repeated Evolution: Varietiesmentioning
confidence: 99%
“…Importantly, our model that gene acquisition is affected by recipient genome content is consistent with the observed enrichment of HGT among close relatives, which presumably have similar genome content (Gogarten et al 2002;Andam and Gogarten 2011;). This taxonomic clustering of innovation by HGT is also in agreement with previous studies that demonstrated that phenotypic and genetic parallel evolution is more common than convergent evolution, potentially due to the effects of historical contingency (Gould and Lewontin 1979;Conte et al 2012;Christin et al 2015;Ord and Summers 2015). However, in contrast to other studies, we present direct evidence that the mechanism by which contingency controls evolution is epistasis.…”
Section: Discussionsupporting
confidence: 93%
“…This predictability is consistent with the hypothesis that genegene dependencies constrain the evolution of genomes by HGT. More broadly, this analysis and our finding that PGCEs can predictably determine future evolutionary gains provide substantial evidence that the preponderance of parallel evolution over convergent evolution (Conte et al 2012;Ord and Summers 2015) may be the result of specific, identifiable genetic dependencies entraining the evolutionary trajectory taken by similar genomes. 8.04…”
Section: Evolution By Hgt Is Predictablementioning
confidence: 62%
See 1 more Smart Citation